A dynamic piezoelectric effect to promote electrosynthesis of hydrogen peroxide. Issue 1 (8th December 2022) - Yang, Hongyuan; Wu, Jie; Chen, Zhengran; Zou, Kai; Liang, Ruihong; Kang, Zhenhui; Menezes, Prashanth W.; Chen, Ziliang
Abstract : The fluid mechanical stress-induced piezoelectric effect could remarkably boost the 2e − oxygen reduction reaction (ORR) performance of PZT ceramics during dynamic operation. Abstract : Physical field modulation has been regarded as a promising approach to boost the performance of various electrocatalysts and has recently received notable attention. However, such a technique by coupling an external field to controllably enable efficient and green electrosynthesis of hydrogen peroxide (H2 O2 ) through a 2e − oxygen reduction reaction (ORR) has not been perceived so far. In order to address the feasibility of this method, a controllable piezoelectric strategy based on the response of intrinsic electric domains to the stimulation of fluid mechanical force was exploited effectively to induce local electric fields on the polarized ceramic catalyst surface during the dynamic ORR. By adjusting the polarization degree of ceramic catalysts, the strength of the local electric field could be accordingly modulated, thus tuning the coverage of OH − ions on the catalyst surface which is beneficial for optimizing the binding strength towards oxygen-containing intermediates and alleviating the disproportionation of the peroxide product.